Police and mental health clinician partnership in response to mental health crisis: A qualitative study. (4th June 2015) - McKenna, Brian; Furness, Trentham; Oakes, Jane; Brown, Steve
Abstract Police officers as first responders to acute mental health crisis in the community, commonly transport people in mental health crisis to a hospital emergency department. However, emergency departments are not the optimal environments to provide assessment and care to those experiencing mental health crises. In 2012, the Northern Police and Clinician Emergency Response (NPACER) team combining police and mental health clinicians was created to reduce behavioural escalation and provide better outcomes for people with mental health needs through diversion to appropriate mental health and community services. The aim of this study was to describe the perceptions of major stakeholders on the ability of the team to reduce behavioural escalation and improve the service utilization of people in mental health crisis. Responses of a purposive sample of 17 people (carer or consumer advisors, mental health or emergency department staff, and police or ambulance officers) who had knowledge of, or had interfaced with, the NPACER were thematically analyzed after one‐to‐one semistructured interviews. Themes emerged about the challenge created by a stand‐alone police response, with the collaborative strengths of the NPACER (communication, information sharing, and knowledge/skill development) seen as the solution. Themes on improvements in service utilization were revealed at the point of community contact, in police stations, transition through the emergency department, and admission to acute inpatient units. The NPACER enabled emergency department diversion, direct access to inpatient mental health services, reduced police officer 'down‐time', improved interagency collaboration and knowledge transfer, and improvements in service utilization and transition.